Analisis Faktor-faktor yang Memengaruhi Harga Minyak Goreng di Indonesia - Maolia, Ishlah Firadina (Universitas Galuh, 2025)
The aim of the research is to determine the influence of world CPO prices, cooking oil consumption, and cooking oil stocks on the price of cooking oil. The research method used is a quantitative method, which this research includes inference statistics. The research location was determined based on three things, namely that since 2012 Indonesia has become the largest exporter of CPO in the world, there are 74 cooking oil factories in Indonesia, and there has been an increase in the price of cooking oil in Indonesia. All data collection was carried out by means of a literature study, where the data used was obtained from various sources, namely National PIHPS, Bappepti, and GAPKI. Sampling was carried out using the purposive sampling method. The data analysis used is multiple linear regression. The research results obtained were divided into three. First, it was found that the world CPO price variable had an insignificant positive influence on the price of cooking oil in Indonesia with a significance value of 0.115. Second, the results show that the variable consumption of cooking oil in Indonesia has a real positive influence on the price of cooking oil in Indonesia with a significance value of 0.000. And third, the results showed that the cooking oil stock variable in Indonesia had an insignificant negative influence on the price of cooking oil in Indonesia with a significance value of 0.484.